The Association of Hydration Status and Other Occupational Factors with Attention, Concentration, and Working Memory among Mine Workers - Adrian Cristianto Yusuf; Dewi Friska; Yetty Ramli; Pukovisa Prawiroharjo; Agus Sugiharto (ILUNI MKK FKUI and PRODI MKK FKUI, 2026)
Background: Hot work environments and poor hydration status may impair workers’ cognitive functions, particularly attention, concentration, and working memory, increasing the risks of operational errors and unsafe behaviors. In open-pit coal mining, heat exposure, high workload, and operational demands contribute to elevated incident rates.Objective: This study aimed to examine the association between hydration status and occupational factors with attention, concentration, and working memory among mine workers at PT. X.Methods: This analytic observational study employed a cross-sectional design among 90 morning-shift coal miners at PT. X, East Kalimantan, recruited using convenience sampling. Cognitive function was assessed using the Digit Span Test, with the Forward Digit Span (FDS) subtest assessing attention and concentration and Backward Digit Span (BDS) subtest assessing working memory. Hydration status was assessed using Urine Specific Gravity (USG) to determine hydration trends over three consecutive days, and perceived stress was measured using the Perceived Stress Scale-10 (PSS-10).Results: The result showed significant associations between hydration status and attention and concentration (p=0.023), as well as working memory (p=0.019). Job type, workload, and work climate were also significantly associated with attention, concentration, and working memory. No change in hydration status trends were observed during the three-day measurement period, with a consistent median USG value of 1,018, indicating mild dehydration. Conclusion: Hydration status, job type, workload, and hot work climate were significantly associated with attention, concentration, and working memory, whereas age, sex, health status, and perceived stress did not show consistent associations with cognitive outcomes.